Instructional Design of Mathematical Modeling in High School Under the STEAM Concept (Journal of Education and Development, 2022)
This paper's focuses on how to design and implement a high school mathematical modeling class under the STEAM concept. STEAM, as an international emerging talent cultivation concept, can cultivate students' interdisciplinary cooperation and innovation ability, and it overcomes the shortcomings of the current mathematics class in China, which is less practical, and uses the knowledge of multiple disciplines to solve practical problems in the form of integrated practical activities. Using the case study method, the author compiled the design ideas and several important aspects of mathematical modeling projects under the STEAM concept, and made three suggestions for the integration of mathematical modeling and STEAM.